Pengaruh Orientasi CSR, Sikap, Dan Kompetensi Terhadap Peran Karyawan Pada PT Bank Pembangunan Daerah Jawa Timur Tbk Surabaya - Shelvia, Mufidatus (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
This study aims to find out and explain the influence of CSR Orientation, Attitude, and Competence on the Role of Employees at PT East Java Regional Development Bank Tbk Surabaya. This study uses a quantitative approach to employees using the Probability Sampling sample, namely the Proportionate Stratified Random Sampling of 62 employees. Statistical analysis used is Structural Equational Modeling (SEM) through SmartPLS Software version 3.2.8. The results of this study indicate that CSR orientation has a significant positive effect on the Role of Employees, Attitudes have a significant positive effect on the Role of Employees, while Competence does not significantly influence the Role of Employees.